Pemahaman Umat Muslim Tentang Distribusi Kekayaan dalam Ekonomi Islam: Studi Fenomenologi Tentang Pemerataan Ekonomi - Muhammad Syahrul Hidayat (Sekolah Tinggi Ilmu Syariah (STIS) Ummul Ayman Pidie Jaya, Ace, 2023)
This research raises a crucial issue in the context of Islamic economics, namely the understanding of Muslims on the distribution of wealth and the phenomenon of economic equity. Using a phenomenological study approach, this research seeks to gain in-depth insight into the perceptions, views and experiences of Muslims regarding this issue. Through in-depth interviews and participatory observation, qualitative data were obtained to be analyzed descriptively and thematically. The results of this study provide a deep understanding of the thoughts of Muslims towards the distribution of wealth in the Islamic economic paradigm. Within the framework of the concept of economic equity, this study explores the essential aspects that influence the perceptions of Muslims in the context of wealth distribution. The findings of this study also provide a more holistic understanding of the phenomenon of economic equity in Islamic economics. This research has significant implications in developing an understanding of the principles of wealth distribution in Islamic economics. The results of these findings can contribute to the development of more inclusive and just economic policies in Muslim societies. By considering the interests and needs of Muslims, this research encourages the efforts of the government and policy makers to promote economic equality as a strategic step in achieving better social and economic justice.